2023
DOI: 10.3389/fmicb.2023.1158731
|View full text |Cite
|
Sign up to set email alerts
|

Microbial gradual shifts during the process of species replacement in Taihang Mountain

Abstract: IntroductionUnderstanding microbial gradual shifts along species replacement can help elucidate the mechanisms driving secondary succession, and predict microbial responses to changing environments. However, how climate-induced species replacement alters microbial processes, and whether microbial shifts follow predictable assembly trajectories remain unclear.MethodsUsing space-for-time substitution approach, we studied shifts in bacterial and fungal communities in the succession from Leptodermis oblonga to Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…For example, Zhou and Zhang (1996) reported that widespread drought driven by high temperatures or low precipitations could lead to substantial forest decline, or replacement of drought-vulnerable with drought-tolerant species (Falk et al, 2019). As temperature rise and water availability decreases (Liu et al, 2023), the more drought-tolerant V. negundo var. heterophylla becomes the most dominant species in the hilly area of Taihang Mountain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Zhou and Zhang (1996) reported that widespread drought driven by high temperatures or low precipitations could lead to substantial forest decline, or replacement of drought-vulnerable with drought-tolerant species (Falk et al, 2019). As temperature rise and water availability decreases (Liu et al, 2023), the more drought-tolerant V. negundo var. heterophylla becomes the most dominant species in the hilly area of Taihang Mountain.…”
Section: Discussionmentioning
confidence: 99%
“…The climate is temperate continental monsoon, with warm summers and cool winters. Annual precipitation averages 519 mm, ranging from 200 to 1129 mm, with 74% falling between June and September (Liu et al, 2023). The monthly mean air temperature (1962-2020) was -3.07°C in January and 26.8°C in July (Liu et al, 2023).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations